AKSELERASI PEMBENTUKAN WILAYAH PERTAMBANGAN RAKYAT DALAM FORMULASI KEBIJAKAN PERTAMBANGAN PASCA UU NO.3 TAHUN 2020 DI BANGKA BELITUNG - Yosua Sandi R. Sembiring; Aramadanna; Fathiyah Umaini; Nabila Azzahra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Tin mining has become part of the potential, challenge, as well as the daily life of the people and local government of Bangka Belitung. As the largest tin-producing region in Indonesia and the second in the world, the Bangka Belitung government has a strong interest in ensuring that mining governance is sound, sustainable, and economically prospective, in accordance with the delegated authority. The issuance of Law No. 3 of 2020 and Presidential Regulation No. 55 of 2022 firmly separates the authority of the central and regional governments. One of the regional authorities is in the field of People's Mining Permits (IPR). Although the IPR mechanism has been regulated in Law No. 4 of 2009, its implementation is still lame in the Serumpun Sebalai Country. The number of illegal tin miners continues to grow, while the number of IPRs used is still very limited. For this reason, by delegating IPR back to the regions, the Bangka Belitung government must prepare a new mechanism to ensure that the IPR network can be carried out optimally. By using a normative approach, this study focuses on the problems of smallholder tin mining and finds alternative strategic and prospective solutions to overcome them.